A Psychometric Study of the Student Evidence-Based Practice Scale S-EBPQ-Arabic Version for Use among Undergraduate Nursing Students - Basmah F. Alharbi (International Journal of Clinical Practice)
Background. Previous studies have demonstrated the significance of evidence-based practice in improving patient care and outcomes. Therefore, integrating evidence-based practice into the health professions’ education curriculum has become a pedagogical priority. However, there is a lack of reliable and valid scales to measure students’ evidence-based practice usage, attitudes, knowledge, and skills in Arab countries. Aim. This study aims to examine the adapted Student Evidence-Based Practice Scale Questionnaire (S-EBPQ) validity at logical statistical level and reliability for use among students in Arabic context. Methods. This cross-sectional study included 233 undergraduate nursing students from a university in Saudi Arabia, who were recruited after translating and pilot testing the S-EBPQ. Three distinctive types of validity including conceptual, content, and face validity were assessed to determine the quality of the questionnaire items logically. Exploratory factor analyses were performed to examine the tool’s structural validity. Additionally, internal consistency was assessed to evaluate reliability. Findings. All items were considered relevant to Arab culture, and no changes were made to any items. The content validity indices for all items were above 0.80 as this was considered an acceptable value. The exploratory factor analysis identified the same four factors (practice, attitude, retrieving and reviewing evidence, and sharing and applying evidence-based practice). All KMO values for the individual items ≥0.876 were also well above the acceptable 0.6 limit. The four-factor structure explained a total variance of 64%, with factor load score λ ≥ 0.455. The total and subscale S-EBPQ scores showed evidence of reliability, with Cronbach’s alpha ≥0.8. Conclusions. This study demonstrated the reliability and validity of the Arabic S-EBPQ version. The study has the potential to advance Arab countries’ understanding of evidence-based practice. S-EBPQ is a validated tool that can be used to assess nursing students’ knowledge of EBP practices. Since educators need to continually evaluate instructional and curricular design in order to meet contemporary nursing needs, this scale can enhance the educational process and enhance students’ competencies.